Novel device therapies in heart failure: focus on patient selection - Balgobind, Amrita; Asemota, Daniel; Rodriguez, Emily; Wattanachayakul, Phuuwadith; Fudim, Marat; Alvarez Villela, Miguel (Frontiers in Cardiovascular Medicine, 2025)
The increasing prevalence of heart failure (HF) has led to advancements in therapeutic strategies, including the development of new pharmacological treatments and the expansion of guideline recommendations across the spectrum of left ventricular ejection fractions. Despite these advancements, the full benefits of guideline-directed medical therapy (GDMT) are often limited by various barriers that result in incomplete implementation or suboptimal responses. For patients who cannot tolerate or only partially respond to GDMT, therapeutic options remain limited. This gap is particularly significant for those with contraindications to heart replacement therapies (HRT), such as left ventricular assist device (LVAD) or heart transplant. In light of these potential limitations, this review article proposes categorizing HF patients into four distinct phenoprofiles based on their tolerance to GDMT and candidacy for HRT. Considering these HF phenoprofiles may guide treatment decisions regarding the selection and use of novel device-based HF therapies. Furthermore, we summarize data on commercially available and emerging device-based HF therapies, evaluating their clinical utility, mechanisms of action, and selection criteria based on current evidence. Finally, we describe clinical cases across various proposed HF phenoprofiles to illustrate how these HF profiles can guide the use of novel device-based therapies to achieve clinical stability, improve GDMT tolerance, or serve as a bridge to, or be used in tandem with HRT in select patients.